Gender Representation in English On Sky 1: A Seventh Grade English Textbook - Sani, Hasrul (STKIP Yapis Dompu, 2022)
This study aims to determine the gender representation in English on Sky 1: a seventh grade English textbook. Specifically, this study sought answers to the following questions: 1) What gender representation in the textbook that are related to illustration, theme and language? 2) Is gender equally represented in the textbook? 3) How do these representations related to Indonesian culture? 4) What activities on teaching gender-equality can be formulated? Based on the result investigation, there is unequal representation of gender in the textbook. The book is dominated by female figures all throughout in terms of illustration, theme and language used. A total number of 297 female figures were noted against 252 males. The distributions are as follows: unit 1, 32 males (12.70%) and 41 females (13.80%); unit 2, 36 males (14.29%)and 49 females (16.50%); units 3, with 34 males (13.49%) and 52 females (17.51%); unit 4, 64 males (25.40%) and 54 females (18.18%); unit 5, 16 males (6.35%) and 21 females (7.07%); unit 6, with 45 males (17.86%) and 50 females (16.84%), and lastly, unit 7, with 25 males (9.92%) and 30 females (10.10%). Females are more visible in roles and role models. The female dominance was found in illustration and language used. This is probably because the author tried to minimize gender bias, not knowing that the number of females have already outnumbered males. Based on the findings, the following conclusions were drawn: The textbook is female-dominated in terms of illustration, theme and language used; gender is not equally represented in the textbook; the author was aware of gender-bias issue in Indonesia.